(untitled) (Scientific journal of the Fergana State University, 2026)
This study explores the impact of Artificial Intelligence (AI) tools on the self-esteem of English as a Foreign Language (EFL) learners at Fergana State University and TATU Fergana Branch. Using a quantitative, descriptive design, data were collected from 56 participants through a structured survey. The results revealed that 85.71% of students reported increased confidence in their English abilities, while 92.85% acknowledged that AI positively contributed to skill development. Daily AI use was reported by 78.57% of respondents, indicating strong engagement. The findings confirm that personalized, adaptive AI tools enhance learners’ self-esteem, motivation, and language performance. However, concerns about reduced human interaction and digital competence gaps remain. The study emphasizes the importance of integrating AI thoughtfully into English instruction, alongside teacher training and ethical safeguards. Future research should explore long-term effects and combine quantitative data with interviews for deeper insights.